Aplikasi Sistem Pakar Diagnosa Penyakit Akibat Suntik Putih Dosis Tinggi Pada Wanita Menggunakan Metode Dempster Shafer - Sukur Niawan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
White injection is a trend of society at this time, not only for young people but also many parents who do this white injection. White injection is a combination of vitamin C solution and other ingredients, such as gluthatione or collagen. There are many types of white injection products that can be used to brighten the skin. One of the most popular white injections is vitamin C. The design of this expert system application can help users in dealing with problems that are often faced, namely the consequences of not paying attention to the level of security in skin beauty treatment. Nowadays, there are many people who offer white injections even without any medical background. Though white injection is not an easy matter that can be done by anyone. This study outlines the Dempster Shafer method that will display the amount of confidence in the symptoms of the possibility of kidney disease suffered by the user. The amount of the trust value is the result of calculations using the Dempster-Shafer method